2002
DOI: 10.1302/0301-620x.84b1.11951
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of loosening of the glenoid component

Abstract: The incidence of loosening of a cemented glenoid component in total shoulder arthroplasty, detected by means of radiolucent lines or positional shift of the component on true anteroposterior radiographs, has been reported to be between 0% and 44%. Radiolucent lines are, however, difficult to detect and to interpret because of the mobility of the shoulder girdle and the obliquity of the glenoid which hinder standardisation of radiographs. We examined radiolucencies around cemented glenoid components in 48 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 19 publications
2
41
0
Order By: Relevance
“…Recent studies performed using radiostereometric analysis with tantalum markers imbedded in both the glenoid and polyethylene glenoid components have not demonstrated a correlation between early radiolucencies and subsequent component migration. 12,16 Other studies have shown some correlation between periprosthetic lucency and implant loosening. 1,3,8,19 The location of the radiolucencies may be an important prognostic indicator of future implant loosening.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies performed using radiostereometric analysis with tantalum markers imbedded in both the glenoid and polyethylene glenoid components have not demonstrated a correlation between early radiolucencies and subsequent component migration. 12,16 Other studies have shown some correlation between periprosthetic lucency and implant loosening. 1,3,8,19 The location of the radiolucencies may be an important prognostic indicator of future implant loosening.…”
Section: Discussionmentioning
confidence: 99%
“…Radiolucent lines surrounding the glenoid component can indicate, but does not necessarily suggest, loosening. As defined by Nagels et al, radiolucency 2 mm or more or a shift in the component suggests radiologic loosening [43].…”
Section: Looseningmentioning
confidence: 98%
“…It is worth noting that lucency surrounding the glenoid component does not necessarily imply glenoid loosening. Nagels et al 33 severe if they involve more than two-thirds. Classification is important because mild and moderate deficiencies are often suitable for component reimplantation with or without bone grafting of the glenoid whereas severe central or combined deficiencies often preclude implantation of new components.…”
Section: Glenoid Lucency After Primary Tsamentioning
confidence: 99%